Evidence of cold water immersion in team sports recovery: a systematic review - Garcia, Cíntia Aparecida (2017)
Objective: Systematically reviewing the effects of cold water immersion recovery on performance of team sports. Methods: Was searched the electronic database National Library of Medicine (PubMed), without date limitations with the following descriptors: cryotherapy and “cold water immersion” combined with sports, “recovery strategies”, “muscle damage”, soft tissue injuries and athletic performance. Eligible studies should be original research, involve team sports, and apply cold water immersion after the exercise session in lower limbs. Results: In all, 22 studies were identified. Large heterogeneity in methodological design and exercise protocols was identified. The population in the studies included rugby athletes; basketball players; football players; futsal players; soccer, handball, hockey and volleyball athletes and team-sport athletes unspecified. Conclusions: From the current results, suggests positives effects of cold water immersion on perception of recovery. To power, sprint, force production and heart rate the results are less clear. Further studies should be conducted to evaluate only the acute effect of CWI after exercise protocols.